Energy-saving of building envelope using passive PCM technique: A case study of Kuwait City climate conditions. (August 2021) - Al-Rashed, Abdullah A.A.A.; Alnaqi, Abdulwahab A.; Alsarraf, Jalal
Abstract: In the Kuwaiti climate region, the residential sector accounts for 64% of electricity consumption. Due to the hot climate for this region, the share of cooling power usage to meet the ventilation requirements in residential buildings is significant. One of the effective methods to reduce power usage is to reduce heat gain. In this numerical study, taking into account the Kuwait City climate region, a PCM layer with a thickness of 20 mm was added to the vertical walls as well as the roof to examine the heat exchange reduction. In the warmeth month (July) by adding PCM of RT-42 to the roof, the heat gain reduced by 15.37%, while this figure for vertical walls was approximately 13.78% which implies that the geographical direction has not considerable effects on PCM usefulness. To investigate the effects of melting temperature on heat gain, three PCMs of RT-31 (phase change temperature of 27–33 °C), RT-35 (29–36 °C and RT-42 (38–43 °C) were examined. Annual calculations showed that RT-31 effectiveness was better than other PCMs so that loading RT-31 into vertical walls + roof resulted in energy saving as well as CO2 saving by 481 kWh m 2 . y e a r and 198.65 k g C O 2 m 2 . y e a r, respectively.